Carbon monoxide-releasing molecule-2 suppresses thrombomodulin and endothelial protein C receptor expression of human umbilical vein endothelial cells induced by lipopolysaccharide in vitro. Issue 21 (May 2017) - Meng, Xianglin; Fei, Dongsheng; Liu, Mingming; Yang, Songlin; Song, Ning; Jiang, Lei; Kang, Kai; Nan, Chuanchuan; Luo, Yunpeng; Pan, Shangha; Zhao, Mingyan
Abstract: Objective: The aim of this study was to observe the counter-effect of carbon monoxide-releasing molecule-2 (CORM-2) on lipopolysaccharide (LPS)-suppressed thrombomodulin (TM) and endothelial protein C receptor (EPCR) expressions from human umbilical vein endothelial cell (HUVEC), and to reveal its mechanisms. Methods: HUVECs were divided into 5 treatment groups, wherein reagents were added simultaneously. TM and EPCR proteins of the cells and the culture medium levels of soluble TM, soluble EPCR, and matrix metalloproteinase-2 (MMP-2) were detected after administration, whereas mRNA levels of TM and EPCR, as well as nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activity among groups, were also evaluated. Results: No significant difference was observed in any indicator between CORM-2 and sham groups. Addition of LPS produced drastic increase in MMP-2 expression, NF-κB activity, shedding of TM and EPCR (into the culture medium), as well as remarkable decrease in both mRNA and protein expressions of TM and EPCR, and cell viability. LPS + CORM-2 treatment significantly reduced the increase in MMP-2, NF-κB activity, and TM/EPCR shedding, whereas maintained both mRNA and protein levels of TM and EPCR, and preserved cell viability. Conclusions: CORM-2 protects HUVEC from LPS-induced injury, by way of suppressing NF-κB activity, which downregulates TM and EPCR mRNAs. It also decreases MMP-2 expression and prevents the shedding of TM and EPCR from the surface of endothelial cells, so as to preserve their protective effect.